Proposed Special Education Paradigm for Mental Disability People in Palestine in the Light of International Trends and Standards - Salha, Soheil Hussein; Albustami, Salam Radi (Journal of Educational and Psychological Sciences, 2020)
As the title indicates, this study has sought to build a paradigm for special education in Palestine to serve people with mental health disabilities in line with international trends and standards. To that end, the researchers first made a review of relevant theoretical literature, such as articles, theses and dissertations, related to curricula and special needs and traits of mentally disabled persons. This is in addition to societies and institutions which cater to their needs. Then based on collected data, the researchers developed a paradigm for special education in the light of contemporary trends and standards in line with official educational policies in Palestine and in harmony with the social, cognitive and skilful frameworks of the mentally disabled individuals. In addition to the proposed paradigm, the researchers have suggested a set of skills and guidelines for school teachers in accordance with the curriculum paradigm. The researchers recommend adoption of the proposed special education paradigm and make it a basis for the production of educational manuals, school textbooks and extracurricular activities in order to raise the quality of education provided to the mentally disabled people.